Local Wisdom on Urban Tourism : (Surakarta Urban Art Corridor Case Study) - Zakiya, Rifda Lushiya; Rini, Erma Fitria; Utomo, Rizon Pamardhi (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2025)
Surakarta is a high tourist attraction due to its local wisdom, associated with tangible and intangible cultural heritage. Gatot Subroto-Ngarsopuro corridor in Surakarta is the regional tourism development area (KPPD) and regional tourism strategic area (KSPD) with urban art urban tourism concept. Urban art aims to enhance the beauty of a city by strenghtening the cityâ€™s attractiveness and characteristics. The concept of urban tourism has elements that need to be considered, which can be a measure of its success. This paper aims to determine the suitability of urban art in the Gatot Subroto-Ngarsopuro Corridor of Surakarta to the components of urban tourism. This research uses a deductive approach with a quantitative descriptive research type applied with two components of suitability, namely the availability and existence of urban art in meeting the components of urban tourism. Based on the result of suitability scoring, it shows that the percentage of suitability is 86,66%, which indicates that the Gatot Subroto-Ngarsopuro Street Corridor of Surakarta City has very high suitability in its role as urban tourism. Â